Estimated dose rates to members of the public from external exposure to patients with 131I thyroid treatment. Issue 4 (25th March 2015) - Dewji, S.; Bellamy, M.; Hertel, N.; Leggett, R.; Sherbini, S.; Saba, M.; Eckerman, K.
Abstract : Purpose: Estimated dose rates that may result from exposure to patients who had been administered iodine‐131 ( 131 I) as part of medical therapy were calculated. These effective dose rate estimates were compared with simplified assumptions under United States Nuclear Regulatory Commission Regulatory Guide 8.39, which does not consider body tissue attenuation nor time‐dependent redistribution and excretion of the administered 131 I. Methods: Dose rates were estimated for members of the public potentially exposed to external irradiation from patients recently treated with 131 I. Tissue attenuation and iodine biokinetics were considered in the patient in a larger comprehensive effort to improve external dose rate estimates. The external dose rate estimates are based on Monte Carlo simulations using the Phantom with Movable Arms and Legs (PIMAL), previously developed by Oak Ridge National Laboratory and the United States Nuclear Regulatory Commission. PIMAL was employed to model the relative positions of the 131 I patient and members of the public in three exposure scenarios: (1) traveling on a bus in a total of six seated or standing permutations, (2) two nursing home cases where a caregiver is seated at 30 cm from the patient's bedside and a nursing home resident seated 250 cm away from the patient in an adjacent bed, and (3) two hotel cases where the patient and a guest are in adjacent rooms with beds on opposite sides of the common wall, with the patient and guest both in bed and either seated back‐to‐back or lying head to head. The biokinetic model predictions of the retention and distribution of 131 I in the patient assumed a single voiding of urinary bladder contents that occurred during the trip at 2, 4, or 8 h after 131 I administration for the public transportation cases, continuous first‐order voiding for the nursing home cases, and regular periodic voiding at 4, 8, or 12 h after administration for the hotel room cases. Organ specific activities of 131 I in the thyroid, bladder, and combined remaining tissues were calculated as a function of time after administration. Exposures to members of the public were considered for 131 I patients with normal thyroid uptake (peak thyroid uptake of ∼27% of administered 131 I), differentiated thyroid cancer (DTC, 5% uptake), and hyperthyroidism (80% uptake). Results: The scenario with the patient seated behind the member of the public yielded the highest dose rate estimate of seated public transportation exposure cases. The dose rate to the adjacent room guest was highest for the exposure scenario in which the hotel guest and patient are seated by a factor of ∼4 for the normal and differentiated thyroid cancer uptake cases and by a factor of ∼3 for the hyperthyroid case. Conclusions: It was determined that for all modeled cases, the DTC case yielded the lowest external dose rates, whereas the hyperthyroid case yielded the highest dose rates. In estimating external dose to members of the public from patients with 131 I therapy, consideration must be given to (patient‐ and case‐specific) administered 131 I activities and duration of exposure for a more complete estimate. The method implemented here included a detailed calculation model, which provides a means to determine dose rate estimates for a range of scenarios. The method was demonstrated for variations of three scenarios, showing how dose rates are expected to vary with uptake, voiding pattern, and patient location.